Algorithm for the assessment of heavyweight and oversize cargo transportation routes - Petraška, Artūras; Čižiūnienė, Kristina; Jarašūnienė, Aldona; Maruschak, Pavlo; Prentkovskis, Olegas (Journal of Business Economics and Management, 2017)
The improvement of transportation systems and technologic equipment leads to changing technical capabilities of this equipment. With the development of technologies, industrial development is also inevitable, resulting in correspondingly increasing need of transportation of HeavyWeight and OverSize (HW/OS) cargo. The application of a systematic approach in HW/OS cargo transportation processes allows reducing costs of delivery of such a cargo several times, which leads to a dramatic change of economic development and investment attraction conditions. Thus creating a system of criteria for the selection and assessment of HW/OS routes, which would allow selecting the most appropriate route of transportation in terms of cost and time, is expedient for this reason. The algorithm for the assessment of HW/OS cargo transportation routes will be drawn up in this article. This algorithm enables an objective evaluation of HW/OS transportation processes comparing different modes of transport, route segments, cargo transportation and cargo handling technology, and it can be practically applied to any territory.